Genocide against the Yazidis A Legal Study on Victims’ Suffering and the Accountability of ISIS - Hussein, Haneen (Journal of Legal Sciences, 2026)
This paper examines the crime of genocide from both a legal and humanitarian perspective, with a specific focus on the atrocities committed by ISIS against the Yazidi community in Iraq since 2014. These crimes—including mass killings, sexual enslavement, and forced displacement—constitute a clear instance of genocide under the 1948 Convention on the Prevention and Punishment of the Crime of Genocide. The study analyzes the international legal framework defining and criminalizing genocide and assesses its applicability to the Yazidi case, emphasizing the centrality of victims in the pursuit of international criminal justice. It also evaluates the accountability mechanisms available, including the International Criminal Court, ad hoc tribunals, and the exercise of universal jurisdiction by national courts (such as those in Germany). The research highlights the major challenges to accountability, including Iraq’s non-accession to the Rome Statute, deficiencies in domestic legislation, and practical barriers to evidence collection and witness protection. Finally, the paper offers recommendations for enhancing accountability through the adoption of domestic legislation aligned with international law, greater international judicial cooperation, and the promotion of transitional justice mechanisms to ensure reparations for victims and the prevention of future atrocities.